Adsorptive removal of phosphate from aqueous solutions using FeCl3‐immobilized melamine‐formaldehyde‐urea resin - Ozdemir Olgun, Fatos Ayca; Çetin, Pınar (Wiley, 2024)
AbstractThe surplus phosphorus in aquatic environments trigger eutrophication, an irreversible pollution stage marked by the rapid growth of algae and water plants, a decline in dissolved oxygen levels, and the emergence of dead zones. To address this critical issue, this study focuses on the removal of phosphorus in form of phosphate from aqueous solutions. The research involves the synthesis and characterization of FeCl3‐immobilized melamine‐formaldehyde‐urea resin, an innovative adsorbent, its characterization through Fourier transform infrared spectroscopy, and the evaluation of its adsorption capacity based on Langmuir and Freundlich equilibrium models. The experimental adsorption data fits well with pseudo‐second order kinetic model. Optimal adsorption parameters are carried with batch adsorption technique for 60 min using 0.5 g of adsorbent at pH = 2, achieving 15.55 mg g−1 adsorption capacity, and conducting experiments with tap‐water samples to replicate real‐world scenarios. The research findings have the potential to advance sustainable wastewater treatment technologies and contribute to the mitigation of nutrient pollution in aquatic ecosystems, addressing a pressing environmental concern.
Keywords: Fe(III) Chloride; Water Treatment; Adsoption Isotherm; Adsorption; Phosphate Removal